Peningkatan Pemahaman Nilai-Nilai Pancasila dan Prestasi Belajar PKn dengan Metode Pembelajaran Cooperative Learning Model Picture and Picture di MIN 2 Sleman - Ummu Aiman (Jurnal Pendidikan Madrasah, 2018)
This research aims to improve the understanding of the values of Pancasila and improving learning achievement through the implementation of a learning model PKn cooperative learning with the method of picture and picture. This research uses research methods class with action through two cycles consist of introduction, core activities, and cover. The results showed that: (1) the method of cooperative learning model picture and picture can improve understanding of the material values of Pancasila grade 4 at MIN 2 Sleman; (2) an increase in the extent of the success of the results of the study on the understanding of material on the first cycle to the second cycle of 8.0% to the level of success on the first cycle of 80.4% success rate on cycle 2 of 88.4%. Furthermore, the results of this research are expected to improve the understanding of the material values of pancasila continuously at MIN 2 Sleman of Yogyakarta.